Sender-receiver games with cooperation - Françoise Forges; Ulrich Horst (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We consider generalized sender-receiver games in which the sender also has a decision to make, but this decision does not directly affect the receiver. We introduce specific perfect Bayesian equilibria, in which the players agree on a joint decision after that a message has been sent ("talk and cooperate equilibrium", TCE). We establish that a TCE exists provided that the receiver has a "uniform punishment decision" (UPD) against the sender.
Keywords: C72; C65; 330; sender-receiver game; commitment; cooperative solution; individual rationality